A STUDY ON THE INVESTIGATION OF THE TRAVELING WAVE SOLUTIONS OF THE MATHEMATICAL MODELS IN PHYSICS VIA (m + (1/G?))-EXPANSION METHOD - Koç, Dilara Altan; Gasimov, Yusif S.; Bulut, Hasan (Jomard Publishing, 2024)
The Gardner equation models the propagation of dust ion acoustic waves. As a result, it has received extensive attention in the literature. For the first time, the (m + (1/G?))-expansion method is used to establish novel exact wave solutions for the Gardner equation. Solutions can exhibit various types of behavior, which can be visualized using 3D and contour graphs. The results obtained demonstrate that the presented method is powerful, useful, practical, and suitable for examining the model. © 2024, Jomard Publishing. All rights reserved.
Keywords: (m + (1/G?))-expansion method; Gardner equation; mathematical modelling; nonlinear partial differential equation; soliton solution; travelling wave solutions